From eruption scenarios to probabilistic volcanic hazard analysis : an example of the Auckland Volcanic Field, New Zealand - Ang, Pei Shan (2020)
The dichotomy between probabilistic and scenario-based volcanic hazard assessments stems from their opposing strengths and weaknesses. The quantification of uncertainty and lack of bias in the former is balanced against the temporal narrative and communicability of the latter. In this paper we propose a novel methodology to bridge between the two, deriving a pseudo-probabilistic hazard estimate from a suite of dynamic scenarios covering multiple volcanic hazards and transitions in eruptive style, as designed for emergency management purposes, in a monogenetic volcanic field. We use existing and new models for eruption style transitions, which provide probabilities conditional on local environmental conditions, thus obtaining the relative likelihoods of each scenario at every location in the field. The results are interpreted in terms of the probability of various hazards and combinations of hazards arising from various scenarios at critical locations. Conversely, we also demonstrate that it may be possible to optimise the likelihood of the scenario allocations across desired locations for emergency management training purposes.